Processing of Plastic Waste Into Alternative Fuels in The Form of Grounded (Pertalastic) Through Pirolysis Process in Science Laboratory of MTsN 3 West Aceh - Syarifah Ratnawati (Universitas Negeri Medan, 2020)
Plastic is one of human needs in daily life, one of which is as a place for wrapping food and drinks, because plastic is practical, clean, and very easy to meet human needs. Increasing the level of public consumption of plastic will also increase the waste / waste produced. The waste has now become a serious environmental problem because of the increasing amount of plastic waste that exists and the level of danger that can be generated from plastic waste for other living things. In Indonesia, the demand for plastic continues to increase until it increases an average of 200 tons per year. As a result of the increased use of plastic is also increasing plastic waste. From testing utilizing existing plastic waste as mentioned above, shows a comparison that is not much different from kerosene traded on the market both in terms of color, thickness, and combustion process. it is known that polyethylene (PE) plastic with a mass of 500 grams can produce as much as 400 ml kerosene in 30 minutes.